Birds of Maine - Vickery, Peter D., 1949-; Duncan, Charles D.; Sheehan, William J.; Wells, Jeffrey V. (Jeffrey Vance), 1964- (Princeton University Press, 2020)
A comprehensive and beautifully illustrated overview to the birds of Maine The first comprehensive overview of Maine's incredibly rich birdlife in more than seven decades, Birds of Maine is a detailed account of all 464 species recorded in the Pine Tree State. It is also a thoroughly researched, accessible portrait of a region undergoing rapid changes, with southern birds pushing north, northern birds expanding south, and once-absent natives like Atlantic Puffins brought back by innovative conservation techniques pioneered in Maine.Written by the late Peter Vickery in cooperation with a team of leading ornithologists, this guide offers a detailed look at the state's dynamic avifauna--from the Wild Turkey to the Arctic Tern--with information on migration patterns and timing, current status and changes in bird abundance and distribution, and how Maine's geography and shifting climate mold its birdlife. It delves into the conservation status for Maine's birds, as well as the state's unusually textured ornithological history, involving such famous names as John James Audubon and Theodore Roosevelt, and home-grown experts like Cordelia Stanwood and Ralph Palmer. Sidebars explore diverse topics, including the Old Sow whirlpool that draws multitudes of seabirds and the famed Monhegan Island, a mecca for migrant birds.Gorgeously illustrated with watercolors by Lars Jonsson and scores of line drawings by Barry Van Dusen, Birds of Maine is a remarkable guide that birders will rely on for decades to come.